Evaluating Technology-Based Educational Interventions: A Review of Two Projects. (June 2013) - Adamo-Villani, Nicoletta; Dib, Hazar
The article discusses current evaluation methodologies used to assess the usability, user enjoyment, and pedagogical efficacy of virtual learning environments (VLEs) and serious games. It also describes the evaluations of two recently developed projects: a virtual learning environment that employs a fantasy 3D world to engage deaf and hearing children in math- and science-based educational tasks, and a serious game for undergraduate students' learning of sustainable building concepts and practices. Although a growing body of evidence suggests that serious games and VLEs could be advantageous and beneficial as instructional tools, research focused on their role in educational settings still lacks a unified approach to evaluating these interventions. To address this gap, the article provides an overview of current challenges associated with assessing the effectiveness of serious games and VLEs. In addition, the results from two projects provide lessons learned, and are intended to guide future efforts in developing and evaluating similar educational technologies.